2016
DOI: 10.1002/term.2144
|View full text |Cite
|
Sign up to set email alerts
|

A peroxiredoxin-based proteinaceous scaffold for the growth and differentiation of neuronal cells and tumour stem cells in the absence of prodifferentiation agents

Abstract: The use of nanoscale materials in the design of scaffolds for CNS tissue is increasing, due to their ability to promote cell adhesion, to mimic an extracellular matrix microenvironment and to interact with neuronal membranes. In this framework, one of the major challenges when using undifferentiated neural cells is how to control the differentiation process. Here we report the characterization of a scaffold based on the self-assembled nanotubes of a mutant of the protein peroxiredoxin (from Schistosoma mansoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…The involvement of PRDXs in the initiation and progression of human cancer was reported in many studies [13,15,61] and some of them were reported to be differentially expressed in colorectal cancers. However, in most of the studies, the PRDXs were studied separately and only the mRNA level or protein level were investigated.…”
Section: Discussionmentioning
confidence: 98%
“…The involvement of PRDXs in the initiation and progression of human cancer was reported in many studies [13,15,61] and some of them were reported to be differentially expressed in colorectal cancers. However, in most of the studies, the PRDXs were studied separately and only the mRNA level or protein level were investigated.…”
Section: Discussionmentioning
confidence: 98%
“…The neural-like phenotype and the cell networks are especially highlighted by electron micrographs with the formation of long sprouting neurites on both Cys48Ser (II) and Cys47Ser tube substrates (III). Adapted with permission from ref ( 95 ). Copyright 2016 John Wiley & Sons, Ltd.…”
Section: Peroxiredoxin-based Bionanotechnologymentioning
confidence: 99%
“… 92 Finally, bare tubes of stacked Prx rings have been demonstrated to be efficient biological scaffolds for adhesion and differentiation of stem and tumor-derived cells with no need of differentiating supplements. 95 The use of Prx for bionanotechnology purposes is just initiated and more efforts should be made in the future to completely master its morpheein behavior in order to easily access all the oligomeric structures available for Prx. For example, the interfaces involved in the Prx’s nanocage structure are not determined at the atomic level, even though some indications on how to stabilize this array already exist; the employment of this supramolecular oligomer for practical purposes is, at present, limited, but still very promising if one considers the many applications of ferritin-like or virus-like nanocages in biomedicine and nanotechnology reported so far.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations